WAVELENGTH-AGILE ABSORPTION SPECTROSCOPY FOR MEASURING TEMPERATURE AND H2O MOLE FRACTION IN HARSH ENVIRONMENTS - Kranendonk, Laura A. (My University, 2009)
This project develops the necessary tools and methods to measure H2O absorption spectra in harsh environments, and calculate temperature and mole fraction from the measured spectra. Various wavelength-agile sources are designed to obtain absorption spectra. The best performing wavelength-agile laser source for H2O measurements to date is the Fourier-Domain Mode-Locking laser. Specific procedures are highlighted to best accommodate the measurements in the presence of beam steering and thermal emission. A robust method to calculate temperature and absorber mole fraction is also developed. Measurements were taken to quantify accuracy in a shock tube and steady burner (used to stimulate gas turbine conditions). Results from HCCI engine measurements demonstrated the precision of the measurements. Temperature results greater than 1000 K have been shown to be biased low. This is a major concern since the main function of the sensor is high temperature combustion studies. Preliminary studies indicate that using a better database for reference spectra should improve these high temperature results.